2002
DOI: 10.1165/ajrcmb.26.5.4689
|View full text |Cite
|
Sign up to set email alerts
|

Selective p38 Activation in Human Non–Small Cell Lung Cancer

Abstract: The mitogen-activated protein kinase (MAPK) pathways transmit signals from the cell membrane to the nucleus. Activation of MAPK cascades may play a role in malignant transformation. We hypothesized that enhanced expression of one or more of these pathways would occur in human lung cancers. Using Western blot analysis of tissue homogenates from resected non- small cell lung cancers and matched non-neoplastic lung tissue, we determined that only activated p38 was consistently increased in tumor compared with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
136
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 25 publications
11
136
1
1
Order By: Relevance
“…41). Activation of p38 has also been reported in a number of human cancers, including non-small-cell lung carcinomas and colon polyps, as well as in the progression from follicular to diffuse large B cell lymphoma (42)(43)(44). In light of our findings, the fact that these signaling pathways are commonly activated in cancer is promising for reovirus use as a cancer therapy.…”
Section: Discussionsupporting
confidence: 77%
“…41). Activation of p38 has also been reported in a number of human cancers, including non-small-cell lung carcinomas and colon polyps, as well as in the progression from follicular to diffuse large B cell lymphoma (42)(43)(44). In light of our findings, the fact that these signaling pathways are commonly activated in cancer is promising for reovirus use as a cancer therapy.…”
Section: Discussionsupporting
confidence: 77%
“…41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation. This in turn could suggest that different cyclophilins and in particular CypA can function as a molecular switch to modulate p38MAPK signalling to adjust to environmental changes, thus modulating cancer cell survival.…”
Section: Discussionsupporting
confidence: 66%
“…9,10 Similarly, overexpression or activation of p38MAPK has been reported in lymphomas, thyroid neoplasms and human lung tumours. [11][12][13] In addition, inhibition of p38MAPK activity enhances apoptosis and cell sensitivity during administration of chemotherapy drugs. [14][15][16][17] The key regulatory sequence within p38MAPK is Thr180-Gly181-Tyr182, in which Thr and Tyr residues are phosphorylated to increase p38MAPK activity by allowing easier access to its active site.…”
mentioning
confidence: 99%
“…Higher serum and alveolar lavage IL-6 and CXCL8 levels are associated with survival of patient with shorter lung cancer (40). In addition, p38a MAPK is highly activated in NSCLC relative to normal lung tissue (41). CXCL8 is also higher in the serum and cystic fluid from patients with ovarian cancer as compared with healthy patients or those with benign cysts (14) and increased CXCL8 expression correlated with more advanced stages of disease.…”
Section: Discussionmentioning
confidence: 99%